Enhancing Duloxetine With Mirogabalin for Treating Taxane-Induced Peripheral Neuropathy in Advanced Lung Cancer - Yasuhiro Nakajima MD, PhD; Kozo Kuribayashi MD, PhD; Akio Tada MD, PhD; Akichika Nagano MD; Toshiyuki Minami MD, PhD; Arihiko Kanehiro MD, PhD; Takashi Kijima MD, PhD (Cancer Control, 2025)
Introduction Taxane-based cytotoxic anticancer drugs are a cornerstone of advanced lung cancer chemotherapy; however, they often result in chemotherapy-induced peripheral neuropathy (CIPN). Along with prolonged recovery, CIPN may cause irreversible damage. Consequently, dose reduction or discontinuation is justified, potentially impacting therapeutic efficacy. With no established treatment for CIPN, low-dose duloxetine is generally used as a supportive drug. However, studies have shown the potential effect of mirogabalin on CIPN. Therefore, at our hospital, patients with advanced lung cancer experiencing CIPN during taxane-based first-line therapy received low-dose duloxetine, and were subsequently treated with mirogabalin. Methods In this study, we conducted a retrospective observational cohort study of the impact of mirogabalin administration on 14 advanced lung cancer patients when duloxetine alone was deemed insufficient. The median age was 71 years (52-89 years), with 9 male and 5 female patients. The Numerical Rating Scale (NRS) was utilized to evaluate outcomes, and Wilcoxon’s signed rank-sum test was used in statistical analysis. Results The median Numerical Rating Scale (NRS) score decreased from 5.5 (interquartile range [IQR]: 4.5-7.0) before to 4.0 (IQR: 3.0-5.0) after mirogabalin administration ( P = 0.041), indicating significant pain reduction. Conclusion The addition of mirogabalin to duloxetine shows promise in alleviating CIPN in advanced lung cancer patients treated with taxane anticancer agents. These findings warrant further investigation and consideration for their integration into clinical practice for managing CIPN.